Critical Care Management of Myasthenic Crisis: A Case Report - Liliriawati Ananta Kahar (Indonesian Rheumatology Association, 2023)
Background: The annual incidence of myasthenia gravis is 1-2 cases in 100,000 population. 30% of all cases will develop bulbar or respiratory muscle weakness. About 15-20% of myasthenia gravis patients will develop myasthenia crisis. Case presentation: An 18-year-old female patient complained of difficulty swallowing two days ago difficulty swallowing solid and liquid food, and this complaint caused the patient to cough and choke. Complaints were accompanied by difficulty opening the eyelids, especially in the afternoon. Complaints were also accompanied by double vision, especially when looking to the right. There was a nasal sound, and the patient had difficulty pronouncing vocal letters. The patient was admitted to ICU, In the ICU patient was intubated and given plasma exchange therapy. Conclusion: Myasthenic crisis is a neurological emergency that requires prompt diagnosis and treatment. Adequate intensive care, judicious weaning, and extubation decisions, along with specifically targeted therapy, will improve the outcome of myasthenia gravis.